Mindful Hand Hygiene and Self-Guided Training Using a Mobile Phone App. Issue 1 (June 2021) - Cahill, Joan; Kay, Alison; Howard, Vivienne; Mulcahy, Ber; Forde, Mary; George, Siji; Lacey, Gerard; Harte, Richie; Reilly, Frank O; Nolan, Rachel; Fitzpatrick, Fidelma; Ziampra, Eva
This paper presents a preliminary concept for a 'Mobile Phone App' providing training in mindful hand hygiene integrated with the WHO hand hygiene protocol. A range of human factors action research methods were used to specify the preliminary concept. This includes stakeholder interviews, workshops, and participatory co-design/evaluation sessions. Mindfulness enables HCW to focus on the correct procedure for HH, along with addressing the need for self-care. The proposed Mobile Phone App enables training in mindful HH, from home. Mindful HH training forms parts of a wider learner journey which includes addressing self-care and training in PPE donning and doffing. Mindfulness is an inexpensive strategy to reduce stress and improve the quality of the working lives of healthcare workers. However, it is not a substitute for professional counselling services.